2004
DOI: 10.1002/jcp.20256
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor‐2 regulates the synthesis of hyaluronan by human periodontal ligament cells

Abstract: Basic fibroblast growth factor (FGF-2) can enhance biological potentials of periodontal ligament cells and its topical application induces considerable periodontal tissue regeneration in vivo. In this study, we examined the effect of FGF-2 on the production of hyaluronan (HA), an extracellular matrix playing important roles in homeostasis and inflammatory/wound healing responses, by human periodontal ligament (HPDL) cells. An inhibition binding-protein assay revealed that FGF-2 significantly increased HA produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 59 publications
3
53
0
1
Order By: Relevance
“…bFGF has multiple effects on cell proliferation, differentiation, and angiogenesis [58]. Animal studies have shown a link between stress, decreased bFGF, and the severity of periodontal disease [19].…”
Section: Blood Flow To the Gingivamentioning
confidence: 99%
“…bFGF has multiple effects on cell proliferation, differentiation, and angiogenesis [58]. Animal studies have shown a link between stress, decreased bFGF, and the severity of periodontal disease [19].…”
Section: Blood Flow To the Gingivamentioning
confidence: 99%
“…Human PDL (HPDL) cells, dental pulp (HDP) cells, gingival fibroblasts (HGFs), and gingival epithelial cells (HGEs) were cultured according to previously described methods (Murakami et al, 2001(Murakami et al, , 2002Shimabukuro et al, 2005Shimabukuro et al, , 2009). We previously established a mouse PDL cell line, MPDL22, and used this as described in our earlier publication (Yamada et al, 2007).…”
Section: Cell Culture and Induction Of Pdl Cell Cytodifferentiationmentioning
confidence: 99%
“…Each isoform is the product of a separate gene (11,12). In several cellular systems, alteration in HA biosynthesis is correlated with increases in HAS mRNA pools, although the genes involved differ for different cell types (13)(14)(15)(16)(17)(18)(19). In this study we examined the temporal response of HA and HAS mRNA to activation of keratocytes with TGF␤ and mitogens.…”
Section: Hyaluronan (Ha)mentioning
confidence: 99%